O papel do arquivista na defesa dos direitos humanos: em busca de elementos da competência em informação - SILVA, Victor Martins da (2021)
This study aimed to demonstrate the importance of Information Literacy (CoInfo) for citizenship promotion, since it gives the basic requirements of how to receive information and interpret it appropriately and to impose critical sense during contact with the documents. The study is arranged in a comparative method between Vitorino theory (2011) that highlights the dimensions of Information Literacy: Technique, aesthetics, ethics and politics relating to the International Council of Archive (CIA) entitled as Basic Principles on the archivists role in the human rights defense, this method aims to demonstrate the convergent points between the Archivistic principles and the four dimensions of CoInfo. The methodology used to provide theoretical background and research grants is bibliographical. It is characterized as empirical because it is an exploratory research between a document and a theory. The results will show the relationships between theory and documents that prove important facts in the citizenship promotion and the construction of knowledge.